2023
DOI: 10.5194/egusphere-2023-281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scenario set-up and forcing data for impact model evaluation and impact attribution within the third round of the Inter-Sectoral Model Intercomparison Project (ISIMIP3a)

Abstract: Abstract. This paper describes the rationale and the protocol of the first component of the third simulation round of the Inter-Sectoral Impact Model Intercomparison Project (ISIMIP3a, www.isimip.org) and the associated set of climate-related and direct human forcing data (CRF and DHF, respectively). The observation-based climate-related forcings for the first time include high-resolution observational climate forcings derived by orographic downscaling, monthly to hourly coastal water levels, and wind fields a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, such approaches, often based on the idea of pattern scaling of global-mean temperature, can only be used for emulation of ESM outputs, and without adequate ESM training pathways will not be able to capture key features of peak-and-decline or stabilisation pathways. Furthermore, none of those emulators is yet able to provide the full richness of variables, spatial and temporal and cross-variable correlations that ESMs are able to provide -and which are key for a range of specific impact models like those linked together in the ISIMIP project (Frieler et al, 2023;Warszawski et al, 2014). Thus, while emulators will be able to play an increasingly important role, they do not provide sufficient capabilities to address the science and policy questions identified above.…”
Section: Framing Pathways To Be Complemented By Sensitivity Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such approaches, often based on the idea of pattern scaling of global-mean temperature, can only be used for emulation of ESM outputs, and without adequate ESM training pathways will not be able to capture key features of peak-and-decline or stabilisation pathways. Furthermore, none of those emulators is yet able to provide the full richness of variables, spatial and temporal and cross-variable correlations that ESMs are able to provide -and which are key for a range of specific impact models like those linked together in the ISIMIP project (Frieler et al, 2023;Warszawski et al, 2014). Thus, while emulators will be able to play an increasingly important role, they do not provide sufficient capabilities to address the science and policy questions identified above.…”
Section: Framing Pathways To Be Complemented By Sensitivity Mipsmentioning
confidence: 99%
“…Such are hereafter referred to as framing pathways since they frame how ESMs can be run with a consistent set of drivers (emissions, concentrations, land surface states, solar activity etc.) to build a range of climate futures which in turn provide a common framing input to impact and vulnerability studies can be conducted (Frieler et al, 2023;Warszawski et al, 2014). The framing pathways thereby can provide a backbone of integration across the IPCC physical science (Working Group I) and impact (WG II) communities 1 and also to link with socio-economic and mitigation information (WG III) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…individually, within this IPCC framework 29,32 . Two transient historical simulations were performed with seven dynamic re-vegetation models: one experiment using reanalysis climate and historical atmospheric CO 2 forcing ("Factual"), and another employing de-trended historical climate and atmospheric CO 2 xed at 1901 levels ("Counterfactual").…”
Section: Mainmentioning
confidence: 99%
“…In this study, we attribute historical changes in burned area to changes in observed climate (meteorological conditions and CO 2 ) and direct human forcings (ignitions and land-use change) individually, within this IPCC framework 29,32 . Two transient historical simulations were performed with seven dynamic re-vegetation models: one experiment using reanalysis climate and historical atmospheric CO 2 forcing ("Factual"), and another employing de-trended historical climate and atmospheric CO 2 xed at 1901 levels ("Counterfactual").…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation